Research of IEEE 802.11 Standard Signal Propagation Features in Multi Floor Buildings - Japertas, S.; Slanys, R. (Elektronika ir Elektrotechnika, 2013)
In this research paper, 802.11 g/n signals non line-of-sight propagation inside the multifloor building is examined. Tests were carried out to assess the signal losses under these conditions. The D-Link and Trendnet wireless routers were used as signal sources in experiments. The measurements were carried out by fixing the routers in the fourth floor of the building. The signal levels were measured with the spectrum analyzer in the 2, 3, 4 (line-of-sight conditions) and 5 floors of the building. The results were compared with the Motley-Keenan model. A new improved model, which allows assessing these experimental results more accurately, is proposed in this paper. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5404